Effects of trastuzumab and afatinib on kinase activity in gastric cancer cell lines. Issue 4 (10th March 2018) - Keller, Simone; Zwingenberger, Gwen; Ebert, Karolin; Hasenauer, Jan; Wasmuth, Jacqueline; Maier, Dieter; Haffner, Ivonne; Schierle, Katrin; Weirich, Gregor; Luber, Birgit
Abstract : The molecular mechanism of action of the HER2‐targeted antibody trastuzumab is only partially understood, and the direct effects of trastuzumab on the gastric cancer signaling network are unknown. In this study, we compared the molecular effect of trastuzumab and the HER kinase inhibitor afatinib on the receptor tyrosine kinase (RTK) network and the downstream‐acting intracellular kinases in gastric cancer cell lines. The molecular effects of trastuzumab and afatinib on the phosphorylation of 49 RTKs and 43 intracellular kinase phosphorylation sites were investigated in three gastric cancer cell lines (NCI‐N87, MKN1, and MKN7) using proteome profiling. To evaluate these effects, data were analyzed using mixed models and clustering. Moreover, proliferation assays were performed. Our comprehensive quantitative analysis of kinase activity in gastric cancer cell lines indicates that trastuzumab and afatinib selectively influenced the HER family RTKs. The effects of trastuzumab differed between cell lines, depending on the presence of activated HER2. The effects of trastuzumab monotherapy were not transduced to the intracellular kinase network. Afatinib alone or in combination with trastuzumab influenced HER kinases in all cell lines; that is, the effects of monotherapy and combination therapy were transduced to the intracellular kinase network. These results were confirmed by proliferation analysis. Additionally, the MET‐amplified cell line Hs746T was identified as afatinib nonresponder. The dependence of the effect of trastuzumab on the presence of activated HER2 might explain the clinical nonresponse of some patients who are routinely tested for HER2 expression and gene amplification in the clinic but not for HER2 activation. The consistent effects of afatinib on HER RTKs and downstream kinase activation suggest that afatinib might be an effective candidate in the future treatment of patients with gastric cancer irrespective of the presence of activated HER2. However, MET amplification should be taken into account as potential resistance factor. Abstract : Our comprehensive quantitative analysis of kinase activity in the gastric cancer cell lines indicates that trastuzumab and afatinib selectively influenced HER family receptor tyrosine kinases (RTKs). The effects of trastuzumab differed between cell lines, depending on the presence of activated HER2. The effects of trastuzumab monotherapy were not transduced to the intracellular kinase network as the investigated intracellular kinases were not regulated by trastuzumab. Afatinib alone, or in combination with trastuzumab, had effects on HER kinases in all cell lines; that is, the effects of monotherapy and combination therapy were transduced to the intracellular kinase network.